The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/mec.14408
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in brain transcriptome is associated with the expression of female mimicry as a sequential male alternative reproductive tactic in fish

Abstract: Distinct patterns of gene expression often underlie intra- and intersexual differences, and the study of this set of coregulated genes is essential to understand the emergence of complex behavioural phenotypes. Here, we describe the development of a de novo transcriptome and brain gene expression profiles of wild-caught peacock blenny, Salaria pavo, an intertidal fish with sex-role reversal in courtship behaviour (i.e., females are the courting sex) and sequential alternative reproductive tactics in males (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 90 publications
(144 reference statements)
1
11
0
Order By: Relevance
“…Previous studies identified distinct gene expression patterns associated with reproductive phenotypes in fish [32][33][34][35][36][37][38][39]65]. Similarly, we identified DNA methylation patterns that discriminate between non-territorial and territorial males.…”
Section: Identification Of Differentially Methylated Genes Involved Imentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies identified distinct gene expression patterns associated with reproductive phenotypes in fish [32][33][34][35][36][37][38][39]65]. Similarly, we identified DNA methylation patterns that discriminate between non-territorial and territorial males.…”
Section: Identification Of Differentially Methylated Genes Involved Imentioning
confidence: 52%
“…To compare our results with previous studies, we searched the literature on fish alternative reproductive tactics and sex determination for genes that were reported as differentially expressed in alternative reproductive morphs by quantitative PCR, microarray analysis, or transcriptome sequencing[32][33][34][35][36][37][38][39][63][64][65]. Gene names were noted as reported in text, tables or figures and are listed inTable S2.To identify the corresponding genes in round goby, we first identified the zebrafish orthologue on ZFIN wherever possible and retrieved the gene symbol.…”
mentioning
confidence: 99%
“…Alternative reproductive tactics ( ART s) are widespread in the animal kingdom. In this issue of Molecular Ecology, Cardoso, Gonçalves, Goesmann, Canário, and Oliveira () investigate plastic ART s of the peacock blenny ( Salaria pavo ), in which males occur in three morphs: nestholders, sneakers and transitionals between the two former. They apply transcriptome sequencing to answer the question how brain gene expression contributes to sex role‐specific behaviour and to intersex phenotypes.…”
mentioning
confidence: 99%
“…Males of the peacock blenny ( Salaria pavo ) population investigated by Cardoso et al. () can follow three different developmental strategies. Depending on their birth date, they either reproduce directly as territorial nestholder males or they reproduce shortly as parasitic sneaker males and change within their first breeding season to the nestholder morphology (transient strategy) or they reproduce their first season as sneakers and only in their second season as nestholders (sneaker strategy).…”
mentioning
confidence: 99%
See 1 more Smart Citation